The Role of Internal Audit in Risk Management in Bandung Amil Zakat Institutios (LAZ) in The Era of Covid-19 Pandemic - Mey Maemunah; Nopi Hernawati; Ririn Sri Kuntorini; Heliana Heliana (Kajian Akuntansi, 2022)
Abstract. This study aims to analyze the role of internal audit in risk management in the amil zakat institution (LAZ) in the city of Bandung. This study uses descriptive analysis with data collection techniques using primary data obtained from observations, interviews and documentation from related parties. The results of the analysis prove that the amil zakat institution in Bandung has used an online-based collection system and has implemented risk managements well. The internal audit of LAZ has understood and applied the five stages of management phases, namely context formation, risk identification, risk measurement, risk evaluation and risk treatment. Thus, it can be concluded that the role of internal audit in risk management in LAZ Bandung is quite good.